Multidisciplinary collaboration among young specialists: results of an international survey by the emerging EULAR network and other young organisations - Najm, Aurélie (RMD Open, 2020)
BACKGROUND: Multidisciplinary collaboration is defined as a collective work involving multiple disciplines and is common in clinical care and research. Our aim was to describe current clinical and research collaboration among young specialists and to identify unmet needs in this area. METHODS: An online survey was disseminated by email and social media to members of the EMerging EUlar NETwork, the Young Nephrologists’ Platform, the Paediatric Rheumatology European Society Emerging Rheumatologists and Researchers and the European Academy of Allergy and Clinical Immunology Junior Members. RESULTS: Of 303 respondents from 36 countries, 61% were female, 21% were aged below 30 years and 67% were aged 31–40 years. Young rheumatologists were the most represented (39%), followed by young nephrologists (24%), young paediatricians (20%), young allergologists (11%) then young internists (3%) and 3% other specialities. Collaborations were reported frequently by phone and email, also by various combined clinics while common local multidisciplinary meetings were uncommon. 96% would like to develop clinical research collaborations and 69% basic research collaborations. The majority of young specialists would be interested in online (84%) and/or 1–2 days (85%) common courses including case discussion (81%) and training workshops (85%), as well as webinars recorded with several specialists on a specific disease (96%). CONCLUSIONS: This collaborative initiative highlighted wishes from young specialists for developing (1) regular local multidisciplinary meetings to discuss complex patients, (2) clinical research collaboration with combined grants and (3) multidisciplinary online projects such as common courses, webinars and apps.